IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MENGATASI AKSI BULLYING PADA PESERTA DIDIK - Afriani, Lenny; Rahayu Ratna Ningsih, Sri; Chanifudin (LPPM STAI Muhammadiyah Probolinggo, 2024)
In reality, education has two goals, namely to help people become intelligent and to inspire people. Morality is a basic problem that fills the niche of human life anytime and anywhere. Moral damage is widespread among students, teenagers and university students from minor ethical, moral and legal deviations to major legal ones. At that time, one of the cases was bullying or acts of violence. This negative behavior shows that people are vulnerable in an educational environment, with the exception of people due to poor environmental conditions. A culture of intimidation (violence) still occurs in the name of seniority among students, and usually bullying occurs repeatedly, even routinely. The target of this research is to determine the implementation of charactereducation in overcoming bullying behavior. One of the aims of this research is to identify character education values ​​that can change bullying behavior into empathy. This research uses library research and descriptive analysis methods. Secondary data consists of supporting books and scientific journals that are relevant to the research topic. Education Books are the main data source. The research results show that the concept of character education can be implemented in the education system, with the aim of changing bullying behavior into an empathetic attitude. It is also hoped that the findings of this research can provide theoretical and practical contributions in the development of character-based education in schools.